Analysis of The Influence of Services and Procedures of Claim Submission on The Interest of Participants in Islamic Insurance (Case Study in General Takaful for Motor Vehicle Insurance Jakarta 2019) - Faridl Noor Hilal; Nurus Shofiyana (Universitas Darusssalam Gontor, 2019)
The financial industry as the financial support of the state is not only support with the banking industry but also support non-banks industry, one of them is insurance. Islamic insurance is a risk management effort that will occur in the future that applies the concept of Islam in its operations. Accidents and natural disasters can occur at any time, especially when living in a country like Indonesia, people try to minimize financial losses caused by disasters that it can be save with insurance. An understanding of the participants about Polis in Islamic Insurance become a reason of the researcher to analyze the influence of the participant in Islamic Insurance. This research was carried out to determine the influence of services and procedures of claim submission towards participants' interest in Islamic insurance. The method used by researchers was a quantitative descriptive method by looking for significance between variables using a simple formula of multiple correlation, with data collecting techniques those are observation, interview, questionnaire and documentation. With sampling techniques of the population amount 61 respondent with purposive sampling. Based on the results of the analysis and discussion, it can be concluded that Service (X1) and the Claim Submission Procedure (X2) affected customer interest in Sharia Insurance (Y). The Fcounting and Ftable tests showed that the results were significant, that the Fcounting value was greater than Ftable (35.11 > 3.16), while the coefficient of determination was indicated by the R2 value of 0.5476 or 54.76% affecting the interest of customers in Islamic insurance, while 45.24% was influenced by other variables unobserved.